Cross sectional study on prevalence and medication adherence of hypertension and diabetes in a tertiary care hospital in Karimnagar, India - Kalyani, S. Sre Akshaya; Pendota, Srihitha; Katnapally, Abhinay Sharma; Porandla, Dharanija; Bheemreddy, Sandeep (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The study aimed to assess the prevalence of Hypertension (HTN), Diabetes mellitus(DM) and other diseases along with comorbid conditions, disease complications and also to assess medication adherence in a tertiary hospital in Karimnagar, Telangana, India. Methods: A Cross sectional study is performed by analysing a total of 500 patient’s individual case safety reports (ICSR). Prevalence of Hypertension and Diabetes along with most prescribed drugs are analysed. Medication adherence is analysed by using Morisky Medication adherence questionnaire scale (MMAS-4). Results: Patients with past history of DM, HTN and other diseases which was found to be 245 (49%) patients. Patients with highest disease prevalence were found to be with HTN (56.73%), DM (31.83%) followed by other diseases like asthma (8.57%), Cerebrovascular accident (4.89%) etc., Total of 66 Patients were ruled out with comorbid diseases. Patients with HTN+DM (47) were found to be highest followed by DM+HTN+CVA (4). MMAS-4 revealed 208 patients were using medication out of 245 patients with previous history. According to MMAS-4 most of the patients were with medium adherence (76). Prevalent drug used for HTN include Amlodipine and for DM Telmisartan+Hydrochlorthiazide. Conclusions: The study revealed that almost half of the admitted patients were with HTN and DM. The patients were counselled properly to adhere strictly to the prescription. Medication adherence to HTN and DM was found to be good in this study. Since the disease complications were also ruled out, the health care professionals are recommended to spread awareness on DM and HTN and disease management in order to control disease and improve health outcomes.